Epithelial Mucosal Changes and An Inflammation Process of the Cavum Nasi Due to Inhaled Sawdust - Yusmawati Yusran; Humairah Medina Liza Lubis (Universitas Muhammadiyah Yogyakarta, 2023)
Woodworkers are particularly susceptible to inhalation of sawdust exposure. Exposure to sawdust for a long time causes various health problems and causes the damage of the epithelium to a barrier. This study aims to identify whether inhaled sawdust can cause changes in the nasal mucosa and the occurrence of an inflammatory process. This study was a cross-sectional analytical study. Data were collected from July 2021 to January 2022 from the nasal cavity swab of 35 woodworkers who had worked for 1 to 5 years. The assessment was carried out by cytological examination to identify epithelial changes in the form of mild and moderate dysplasia, while the inflammation was found in the form of acute and chronic inflammation. Twenty-six (74.3%) samples were normal, 7 (20%) samples had mild dysplasia, and 2 (5.7%) samples had moderate dysplasia. Whereas 20 (57.1%) were found to have no inflammation, 8 (22.9%) were with acute inflammation, and 7 (20.0%) were found to have chronic inflammation). Fisher’s exact test showed a relationship between the inflammatory process and epithelial changes (p 0.020). In conclusion, sawdust inhaled showed changes in the epithelial mucosa and inflammatory processes of the nasal cavity.